Zeil Neelson and Wade-Fite stains to demonstrate medlar bodies of chromoblastomycosis - Lokuhetty, M.D.S.; Alahakoon, V.S.; Kularatne, B.D.M.U.; De Silva, M.V.C. (My University, 2007)
The characteristic fungal bodies of chromoblastomycosis, known as Medlar bodies, are visualized as golden brown rounded bodies in routine hematoxylin and eosin (H&E) stained tissue sections of the skin (Fig. 1). We report a hither to undocumented staining pattern of Medlar bodies that will be useful when they are not identified in routine H&E stains, in cases with a high index of clinical suspicion.........